Prevalence of hepatitis E virus antibodies in pigs: implications for human infections in village-based subsistence pig farming in the Lao PDR. - Blacksell, S; Myint, K; Khounsy, S; Phruaravanh, M; Mammen, M; Day, N; Newton, P (2007)
We report a high seroprevalence of hepatitis E virus (HEV) in pigs in the Lao PDR. HEV seroprevalence was 51.2% (300/586) amongst abattoir pigs and 15.3% (46/301) amongst village pigs. The age distribution suggested previous in-village HEV pig infections. These findings suggest a zoonotic risk associated with village-based smallholder pig farming.